2014
DOI: 10.1002/jcb.24777
|View full text |Cite
|
Sign up to set email alerts
|

LIF/STAT3/SOCS3 Signaling Pathway in Murine Bone Marrow Stromal Cells Suppresses Osteoblast Differentiation

Abstract: Leukemia inhibitory factor (LIF) is a pleiotropic cytokine that belongs to the interleukin-6 family and is expressed by multiple tissue types. This study analyzed the effect of LIF on osteoblast differentiation using primary murine bone marrow stromal cells (BMSCs). Colony-forming unit-osteoblast formation by BMSCs was significantly suppressed by LIF treatment. To clarify the mechanism underlying the LIF suppressive effect on osteoblast differentiation, we analyzed the downstream signaling pathway of LIF. LIF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…LIF, a pleiotropic cytokine expressed in various tissues, inhibits osteoblast differentiation and induces adipocyte differentiation in fetal rat calvarial cells 31 , 32 . Although several previous animal studies showed that LIF promotes bone formation 33 , 34 , a recent study argued that LIF suppresses osteogenesis by inhibiting β-catenin through the LIF/STAT3/SOCS3 signaling pathway 35 . Consistent with its proposed inhibitory function in bone cell differentiation, we found that siRNA-mediated depletion of LIF activated the maturation potential of MC3T3-E1 pre-osteoblastic cells by increasing ALP activity, ECM mineralization, and the expression of osteoblast-related biomarkers (e.g., Runx2, ALP, and BMP2) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LIF, a pleiotropic cytokine expressed in various tissues, inhibits osteoblast differentiation and induces adipocyte differentiation in fetal rat calvarial cells 31 , 32 . Although several previous animal studies showed that LIF promotes bone formation 33 , 34 , a recent study argued that LIF suppresses osteogenesis by inhibiting β-catenin through the LIF/STAT3/SOCS3 signaling pathway 35 . Consistent with its proposed inhibitory function in bone cell differentiation, we found that siRNA-mediated depletion of LIF activated the maturation potential of MC3T3-E1 pre-osteoblastic cells by increasing ALP activity, ECM mineralization, and the expression of osteoblast-related biomarkers (e.g., Runx2, ALP, and BMP2) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice overexpressing LIF have been noted to exhibit increased osteoclastic bone resorption . Recent studies also suggest a direct inhibitory effect of LIF on osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) by means of STAT3/SOCS3 signaling pathway . Although the effects of muscle‐derived LIF on bone homeostasis have not been reported, it is possible that the elevated LIF protein in dystrophic muscle might also contribute to the bone loss observed in DMD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the expression of Wnt4, a non-canonical Wnt ligand that promotes osteogenesis (Chang et al, 2007), was significantly increased in Prx1-Cre;Lepr fl/fl SSCs ( Figure 7O). Socs3, a downstream target of Stat3 and a negative regulator of osteogenesis (Matsushita et al, 2014), also was significantly reduced in expression in Prx1-Cre;Lepr fl/fl SSCs ( Figure 7O). Consistent with this, qPCR analysis of uncultured PDGFRa + CD45 À Ter119 À CD31 À cells from Prx1-Cre;Jak2 V617F and control mice showed increased expression of Cebpa and Socs3 and decreased expression of Wnt4 ( Figure S6M).…”
Section: Lepr Negatively Regulates Bone Regeneration After Injurymentioning
confidence: 97%